CORRELATION BETWEEN PICKY EATER BEHAVIOR AND RAMPANT CARIES IN PRESCHOOL CHILDREN IN SURABAYA - Putu Agung Narendra Indria Dewi; Wahyuni Dyah Parmasari; Ayling Sanjaya; Siany Suryawati (FKG ULM, 2025)
The dental and oral health of the Indonesian people is still something that needs to be seriously viewed by health workers, both doctors and nurses. In Indonesia, the prevalence of caries in children aged 3-4 years reaches 81,1%, root caries reaches 13,3% and caries ages 5-9 reaches 92,6%, root caries reaches 28,5%, indicating that caries in Indonesia has entered the high category. Caries rampan is caused by multifactorial, where one of these factors is children's eating behavior, children's diets have various patterns, one of which can be seen from children who have picky eater behavior. This research aims to determine the relationship between picky eater behavior and the incidence of caries ramping in preschool children. This research was carried out using an observational analytical method with a cross sectional approach. The results of this study show that preschool age children dominated by women 61,1% and boys 38.9%.children have picky eater behavior as much as 75,0% and caries incidence 86,1%. The study results showed a relationship between picky eater behavior and the incidence of caries rampan in preschool-aged children at Kindergarten Surabaya in 2024 with a chi-square statistical chi-square(⍴=0,002 value). Based on the research conducted, it is hoped that parents and schools will pay attention to children's eating behavior and dental and oral health.